2022
DOI: 10.1002/jts.22895
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder, diurnal cortisol, and ambulatory blood pressure in early and late pregnancy

Abstract: Posttraumatic stress disorder (PTSD) affects 1 in 20 reproductive-aged women and is associated with cardiovascular disease morbidity and mortality. The pathophysiology linking PTSD to cardiovascular disease in nonpregnant adults is proposed to include hypothalamic and autonomic dysregulation; however, the pathways explaining this association in pregnancy are unclear. We examined diurnal cortisol and ambulatory blood pressure (BP) among 254 pregnant women at approximately 12 and 32 gestational weeks. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…38 Our group recently reported that PTSD symptoms in pregnancy were positively associated with maternal (nocturnal) blood pressure in late pregnancy and negatively associated with diurnal cortisol in early pregnancy (although this result did not withstand adjustment for covariates). 39 Results suggest that symptoms of PTSD in pregnancy may increase risk for adverse cardiometabolic outcomes via disruptions in multiple biological and interconnected systems.…”
Section: Discussionmentioning
confidence: 98%
“…38 Our group recently reported that PTSD symptoms in pregnancy were positively associated with maternal (nocturnal) blood pressure in late pregnancy and negatively associated with diurnal cortisol in early pregnancy (although this result did not withstand adjustment for covariates). 39 Results suggest that symptoms of PTSD in pregnancy may increase risk for adverse cardiometabolic outcomes via disruptions in multiple biological and interconnected systems.…”
Section: Discussionmentioning
confidence: 98%